SOCIO-ECONOMIC PROFILE OF MANIPURI PONY OWNERS* (Indian Journal of Animal Production and Management, 2014)
economic profiles of Manipuri Pony owners. During the survey, 215 Manipuri Pony owners and farmers from 3 districts were interviewed using questionnaire. The study on various socio-economic parameters revealed that most of the pony owners belong to 15-55 years age group. About 76.74% of them had passed at least class VIII. In majority of the cases (62.33%), the holding size was 1 animal followed by 23.26% with 2 animals. The survey also revealed most of the owners (56.74%) were not having any land (landless) while 32.56% maintained land up to 1 hectare. It was also known that Pony owners didn’t receive any economic return from pony rearing at present unlike other livestock like dairy, poultry and piggery. The survey further revealed that majority of the pony owners are economically backward and 59.92% of the pony owners depended for their livelihood on agriculture and allied activities.
Keywords: Manipuri Pony; Socio-economic; Population